The innovation of accounting and certification of historic architectural monuments using BIM technology - Kysil, Olga; Kosarevska, Raddamila; Levchenko, Oleksii (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
Presented research shows Building Information Modeling (BIM) technology as a highly promising tool for architectural heritage conservation. Analyses of contemporary publications by BIM topic and HBIM (Historic Building Information Modeling), its specific division, are conducted. The usage of modern technology analysis for digitizing monuments along with the outdated ‘manual’ of accounting and passportization methods are executed, and a lack of automation of the above processes is observed. Additionally, the research reveals that during the operational period of historical objects, there was no method of fixing their architectural transformations. The necessity of automation of the abovementioned processes by the capabilities of the BIM technology is emphasized. Automation methods developed utilizing the BIM model properties as a relational database, are described. An example of the method implementation in architectural and construction software applications is given. The case uses the rules of filling in the state accounting card of Ukraine. Nonetheless, the automatic formation of a document like this by the standards of any country is underscored.